2018
DOI: 10.3892/ol.2018.9076
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CXC motif chemokine receptor 4 inhibits the proliferation, migration and angiogenesis of lung cancer cells

Abstract: An increasing volume of data indicates that disrupting the interaction between CXC motif chemokine receptor 4 (CXCR4) and its specific ligand, CXC motif chemokine 12 (CXCL12), may reduce tumor growth and metastasis. However, the translation from bench to bedside must be performed with extreme caution, as the CXCR4/CXCL12 axis is crucial for the normal development and maintenance of tissues and organs. In the present study, Cell Counting Kit-8 and Transwell migration assays were used to detect proliferation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Lee et al [ 64 ] found that blocking the CXCL12/CXCR4 axis with anti-CXCR4 antibodies could decrease breast cancer cell migration to the brain. It has been reported in an experimental study that blocking CXCR4 inhibited the proliferation of lung cancer cells and the migration to CXCL12 [ 65 ]. In recent experimental studies, CXCR4 expression was shown to mediate cisplatin resistance in a cytochrome P450 1B1 (CYP1B1)-dependent manner way and paclitaxel resistance by increasing the expression of antiapoptotic proteins [ 26 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 64 ] found that blocking the CXCL12/CXCR4 axis with anti-CXCR4 antibodies could decrease breast cancer cell migration to the brain. It has been reported in an experimental study that blocking CXCR4 inhibited the proliferation of lung cancer cells and the migration to CXCL12 [ 65 ]. In recent experimental studies, CXCR4 expression was shown to mediate cisplatin resistance in a cytochrome P450 1B1 (CYP1B1)-dependent manner way and paclitaxel resistance by increasing the expression of antiapoptotic proteins [ 26 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that CXCR4/ CXCL12 participates in cancer development (6,8,(15)(16)(17)(18). CXCR4 is the only chemokine receptor expressed by the majority of cancer cells, and its ligand CXCL12 can be secreted by tumor cells and stromal cells, including tumor-associated fibroblasts (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine expression is stimulated by infection and inflammation, which serves an important role in the attraction, recruitment and activation of leukocytes and immune cells (4,5). C-X-C Motif Chemokine Ligand 12 (CXCL12) represents the natural ligand for C-X-C motif chemokine receptor 4 (CXCR4) and has been indicated to play a role in the metastasis of CXCR4-expressing cells (6)(7)(8). Fibrocytes originate from the bone marrow, and express hematopoietic (CD34+) and mesenchymal markers [collagen I+ (ColI+) and vimentin+] (9).…”
Section: Introductionmentioning
confidence: 99%
“…Forcing CXCR4 overexpression in A549 cells leads to increased invasiveness through the increased expression of VEGF-C, MMP2, and phosphorylation of AKT (Zeng et al 2017). A different group repeated the experiment and found similar results that could be reversed by treatment with a CXCR4 inhibitor (He et al 2018). The co-culture of CAFs with PDAC cells similarly increases invasiveness, which can be nullified by the inhibition of CXCR4 (Bhagat et al 2019), although the authors left the responsible pathway unspecified.…”
Section: Cxcl12/cxcr4mentioning
confidence: 97%